An Exploratory Study on Developers Opinions about Influence in Open Source Software Ecosystems - Condina, Vinicius; Malcher, Paulo; Farias, Victor; Santos, Rodrigo; Fontão, Awdren; Wiese, Igor; Viana, Davi (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Software Engineering researchers and practitioners have sought a systematic way of characterizing technical and social behaviors in software development, from the perspective of either an artifact (e.g. design pattern) or an actor (e.g. developer). In this context, influencers are those who guide the development methods and disseminate patterns due to their popularity or status in the community. Especially in software ecosystems, the dynamics of interactions with interventions of external developers over a common technological platform leverage the effects of influence and still remains as a challenge. This paper presents an exploratory study on the sense of influence in open source software ecosystems, more specifically from the opinions of 95 developers who contribute to npm projects based on GitHub. To do so, qualitative data from a conducted survey research were analyzed based on Grounded Theory (GT) procedures. Based on two main categories (Technical and Social), we recognized aspects that reinforce some key characteristics of an influencer, e.g., 'status in the project', 'participation with code', 'participation with comments ', and 'content value'. However, some diverging aspects were observed, e.g., the difference between qualitative and quantitative responses related to 'long-time interaction with the project'. This study contributes with the identification of influencers' characteristics that can aid both researchers in further studies on open source software ecosystems and practitioners in strategies to manage project-based ecosystems.